Freshwater ecology : concepts and environmental applications of limnology - Dodds, Walter K. (Walter Kennedy), 1958- (Aquatic ecology series., 2010)
The Second Edition of Freshwater Ecology is broad, up-to-date treatment of everything from the basic chemical and physical properties of water to advanced unifying concepts of the community ecology and ecosystem relationships as found in continental waters. With 40% new and expanded coverage, this text covers applied and basic aspects of limnology, now with more emphasis on wetlands and reservoirs than in the previous edition. The authors take a synthetic approach to ecological problems, teaching students how to handle the challenges faced by contemporary aquatic scientists. New to this edition: 80 new and updated figures, including a section of color plates 2 new chapters and expanded coverage throughout 500 new and updated references - Expanded revision of Dodds' successful text. - New boxed sections provide more advanced material within the introductory, modular format of the first edition. - Basic scientific concepts and environmental applications featured throughout. - Added coverage of climate change, ecosystem function, hypertrophic habitats and secondary production. - Expanded coverage of physical limnology, groundwater and wetland habitats. - Expanded coverage of the toxic effects of pharmaceuticals and endocrine disrupters as freshwater pollutants - More on aquatic invertebrates, with more images and pictures of a broader range of organisms - Expanded coverage of the functional roles of filterer feeding, scraping, and shredding organisms, and a new section on omnivores. - Expanded appendix on standard statistical techniques - Supporting website with figures, extra material and exercises.